2018
DOI: 10.1080/16549716.2018.1433987
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and perceived barriers to oral antiviral therapy for chronic hepatitis B

Abstract: Background: Globally, of the 248 million people chronically infected with the hepatitis B virus (HBV), 74 million reside in China. Five oral nucleot(s)ide analogs (NUCs) have been approved for the treatment of chronic hepatitis B (CHB) in China. Objectives: The aims of this study were to determine rates of adherence to NUC therapy in patients with CHB, to identify the self-perceived barriers to adherence, and to examine the factors associated with adherence. Methods: Questionnaire-based interviews were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
1
26
1
2
Order By: Relevance
“…Patients with chronic diseases living in rural areas may have limited access to healthcare services. Previous studies found that knowledge about CHB was low in rural Chinese populations (Yang et al, 2017), and rural patients with CHB had lower medication adherence than urban ones (Xu & Liu, 2018). Self-management of CHB includes complicated tasks, which represents a difficult endeavour for rural patients.…”
Section: Backg Rou N Dmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients with chronic diseases living in rural areas may have limited access to healthcare services. Previous studies found that knowledge about CHB was low in rural Chinese populations (Yang et al, 2017), and rural patients with CHB had lower medication adherence than urban ones (Xu & Liu, 2018). Self-management of CHB includes complicated tasks, which represents a difficult endeavour for rural patients.…”
Section: Backg Rou N Dmentioning
confidence: 96%
“…Effective self‐management mostly depends on the patient's willingness and ability to undertake daily self‐management activities (Wu et al, ). Despite the importance of self‐management, patients with CHB in China were found to be less adherent to self‐management activities, such as low adherence of antiviral drugs, follow‐up visits, abstaining from alcohol and moderate exercise (Lin et al, ; Xu & Liu, ). Exploring factors that influence self‐management activities is important to promote their engagement in self‐management for patients with CHB.…”
Section: Introductionmentioning
confidence: 99%
“…Показано также, что приверженность к лечению, как правило, снижается при увеличении длительности терапии [36,37]. Среди других факторов, ассоциирующихся с приверженностью к терапии, выделяют уровень материального благополучия и образования пациента, количество других принимаемых лекарственных средств, степень взаимодействия врача и пациента [32,35,38,39]. В исследовании Peng и соавт.…”
Section: Discussionunclassified
“…В исследовании Xu и соавт. также показана высокая частота прекращения лечения (в 48,7% случаев) вследствие высокой стоимости препаратов [35]. Таким образом, можно предполагать, что повышение доступности лечения и применение более эффективных и безопасных препаратов будет сопровождаться увеличением показателя "сохранения на терапии" при длительном лечении АН у больных ХГВ.…”
Section: Discussionunclassified
“…Two studies included in our review assessed treatment compliance by measuring drug concentration in plasma (16,41). Studies assessing treatment adherence in chronic HBV have also used questionnaire-based approaches (66)(67)(68), but these are subject to bias as self-. CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Other Factors Associated With Persistent Vireamiamentioning
confidence: 99%